GEREJA YANG BERBAGI DAYA DALAM MISI LINTAS BUDAYA: KAJIAN MISIOLOGIS ROMA 15:22-33 - Paulus Dimas Prabowo; Jhon Kalaka (Manna Rafflesia, 2023)
The church has been chosen as God's mission agent in the time of grace to express God's love for all ethnic groups in the world in a cross-cultural mission program. However, church mission activities (missio ecclesiae) in cross-cultural missions are often interpreted as limited to preaching the gospel by taking Matthew 28:19-20 to be the primary text reference. Evangelicals and Pentecostals widely hold this view. Considering other texts, it will be evident that the local church's involvement in cross-cultural missions is more expansive to include other activities. Through the method of thematic analysis of Romans 15:22-33, through a missiological lens, it is revealed that the church can share power in cross-cultural missions in three ways: accompanying evangelism in the field and donating funds for humanitarian services and praying for ongoing tasks. Church involvement is holistic, touching both spiritual and physical aspects.